PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH MELALUI MEDIA AUDIO VISUAL TERHADAP PENINGKATAN KEMAMPUAN BERPIDATO SISWA KELAS IX SMP NEGERI 1 NUSAHERANG KABUPATEN KUNINGAN - Suherli Kusmana; Endang Kasupardi; Nunu Nurasa (Jurnal Tuturan, 2014)
And result process study of ability orate IX SMP Country class student 1 Nusaherang Sub-Province Brass not yet directional and not yet reached result of optimal. Student ability level in speech is still low. It is caused of implementing not relevant with the student characteristics. The aim of this research is is to effectiveness descriptions model study base on the problem of passing visual audio media to ability orate IX SMP Country class student 1 Nusaherang, influence descriptions model study base on the problem of passing visual audio media to ability orate IX SMP Country class student 1 Nusaherang, and IX SMP Country class student respon descriptions 1 Nusaherang about usage model study base on the problem of passing visual audio media to ability orate. In this research the writer use in esperiment method through pretest-postest control group design. This design consist of two control group. In the process problem based learning is done by experiment group and it will be demonstrated by control group. The measurent is given after the writer make the various conditions to the students. Result of the research indicates that problem based learning by using audio visual media is more effective in improving the student speech ability. It can be drawn by the students activity. All the students learn the material more cooperatively and they have ability in speech in amount 0,8752 = 0,76 (76%) it means that the students speech ability is influenced by implementing problem based learning through audio visual media. Most of the student agree and give positive respons toward implementing problem based learning through audio visual media. The benefit of using this approach: 1) to increase student motivation, 2) to increase student creativity, 3) to awoid boring sense in learning, and (4) to improve respect attitude toward other opinion.